Automatic limit switch calibrator for control valve at steam turbine of a geothermal power plant - Prisma Megantoro; Abdul Latif; Brahmantya Aji Pramudita; P. Vigneshwaran (Institute of Advanced Engineering and Science, 2021)
Measurement of fluid level in steam valves should require precise values. The instrument designed in this article is used to find out how precise the limit switch is used as an indicator control valve at certain points. The measurement technique will be implemented on a control valve on the geothermal power plant. This device is using the Arduino Due board as a data processor and modified the data signal of the vernier caliper to measure the valve opening. The TFT LCD layer is used to display the measurement and calibration results. The test results of this device indicate that this device has an accuracy level of more than 99%.